Defect formation during preforming of a bi-axial non-crimp fabric with a pillar stitch pattern - Chen, S.; McGregor, O.P.L.; Harper, L.T.; Endruweit, A.; Warrior, N.A. (Elsevier, 2016)
To capture the asymmetrical shear behaviour of a bi-axial NCF with a pillar stitch, a non-orthogonal constitutive model was developed and implemented in finite element forming simulations. Preforming experiments indicate that the local distribution of defects is significantly different on both sides of each bi-axial ply, with two different defect mechanisms observed. Correlation with simulation results indicates that one defect type is caused by excessive shear, inducing out-of-plane wrinkling in regions of positive shear (macro-scale wrinkling). The other defect type is caused by fibre compression, inducing in-plane wrinkling in regions of negative shear (meso-scale wrinkling). Local distributions of shear angle and wrinkling strain were used to determine the wrinkling mode and to confirm the corresponding defect mechanism. Results indicate that simulations based on the advanced constitutive model can predict local shear angles within ±5°of experimental values and that predicted wrinkling positions and defect types correlate well with the experiments.